1997
DOI: 10.1152/ajpgi.1997.273.4.g913
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition of Na+-glucose cotransport in the chronically inflamed rabbit ileum

Abstract: In a rabbit model of chronic ileal inflammation, we previously demonstrated that coupled NaCl absorption was reduced because of an inhibition of Cl−/[Formula: see text]but not Na+/H+exchange on the brush-border membrane (BBM) of villus cells. In this study we determined the alterations in Na+-stimulated glucose [Na+- O-methyl-d-glucose (Na+-OMG)] absorption during chronic ileitis. Na+-OMG uptake was reduced in villus cells from the chronically inflamed ileum. Na+-K+-adenosinetriphosphatase (ATPase), which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 14 publications
5
76
0
Order By: Relevance
“…These data also indicated that tissue inflammation was associated with decreased Na + absorption. In animal models of colitis, both hyporesponsiveness to secretagogues (45) and decreased Na + -absorptive processes (Na + -dependent glucose absorption and non-nutrient-dependent Na + and Cl -transport) have been observed (46,47). Similar to the present findings, decreased Na + /K + -ATPase activity was measured in inflamed intestine (48).…”
Section: Discussionsupporting
confidence: 89%
“…These data also indicated that tissue inflammation was associated with decreased Na + absorption. In animal models of colitis, both hyporesponsiveness to secretagogues (45) and decreased Na + -absorptive processes (Na + -dependent glucose absorption and non-nutrient-dependent Na + and Cl -transport) have been observed (46,47). Similar to the present findings, decreased Na + /K + -ATPase activity was measured in inflamed intestine (48).…”
Section: Discussionsupporting
confidence: 89%
“…BBM vesicles (BBMV) from rabbit intestinal villus cells were prepared by CaCl 2 precipitation, and differential centrifugation as previously reported (23,24). BBMV were resuspended in a medium appropriate to each experiment.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…For example, alanine is transported into villus cells by one of these Na-driven amino acid transporters specifically by the Na-neutral amino acid cotransporter system B 0 (Asct1)(3) and will be used to measure the effects of cNO on NAcT. Both cotransporters have been localized to the BBM of the absorptive villus but not the secretory crypt cells in the mammalian small intestine including rabbits (23,24). The favorable transcellular Na gradient for these secondary active transport processes is provided by Na-K-ATPase on the basolateral membrane (BLM) of villus cells (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations